CLINICAL AND DIAGNOSTIC SPECIFICITY OF THE COURSE OF CORONAVIRUS INFECTION IN ELDERLY AND YOUNG PATIENTS VACCINATED AGAINST COVID-19 (Western European Journal of Medicine and Medical Science, 2024)
Due to the lack of specific symptoms of COVID-19 infection, early differential diagnosis with other conditions/diseases is impossible. In the neonatal period, for the management of newborns, the diagnosis of COVID-19 infection should be suspected/marked. following current clinical guidelines for birth and treatment of relevant perinatal conditions. It is also recommended to conduct multidisciplinary consultations (mainly remote) with the participation of a clinical pharmacologist and other narrow specialists for relevant indications.